Feasibility analysis of the veil convection business using value engineering for cost efficiency - Dilla; Amri; Muhammad Zakaria (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
The veil business is a business that operates in the veil manufacturing industry. The products produced vary according to consumer demand and the stock produced. This headscarf product has spread to several areas of Aceh, such as Banda Aceh, Lhokseumawe, and Langsa, especially the Bireuen City area, and has collaborated with several Islamic boarding schools. The headcarf models released by this company greatly influence consumer demand. The better the material, model, and quality, the more consumer demand for convection will increase. This research aims to analyze the feasibility of developing a veil convection business using a value engineering method and financial feasibility. The research results were obtained using the analytical hierarchy process method and vacuum engineering. The chosen alternative is model 1, with a weight of 0.53, a square hijab type, standard material, soft colors, and zipper accessories according to consumer demand. And the results of the financial aspect calculations show that the Ita Hijab convection business has a positive NPV of IDR 29,373,042, with a BEP of 480 units. The payback period for investment capital is 5 months. If you look at the payback period calculation with a BCR value > 1, then the veil convection business is said to be worthy of investment